A Comparative Study on Aluminium Pillared Smectite Synthesis From Synthetic Saponite and Indonesian Montmorillonite - Is Fatimah; Shaobin Wang; Karna Wijaya; Narsito -; Narsito - (ASEAN Journal of Chemical Engineering, 2008)
Synthesis of aluminium pillared smectite from two raw clays, saponite and Indonesian montmorillonite, has been investigated. The clays were characterized by XRD, N2 adsorption isotherm, DTA-TGA, surface acidity measurements using pyridine-FTIR method, and evaluated for catalytic esterification reaction. The characterization indicated an increase in d001 by metal oxide pillar, increase in BET specific surface area, and surface acidity. DTA-curves showed exothermic peaks in the range of 100-130oC and 400-800oC. TGA curves showed an increase in thermal stability of pillared clays. For both kinds of clays, it was also observed that pillarization reduced weight loss at high temperature. Esterification reaction rate constant and surface acidity data showed that the Brønsted acidity dominantly affects the reaction mechanism compared with the effect of specific surface area and Lewis acid site. Montmorillonite and pillared montmorillonite exhibited higher catalytic activity than saponite and pillared saponite although the specific surface areas of the latter are higher.